THE ROLE AND SIGNIFICANCE OF USING INNOVATIVE EDUCATIONAL TECHNOLOGIES IN EDUCATIONAL PROCESSES - Parmanov Abdulla Esanturdievich; Esanturdieva Shahlo Abdulla qizi (American Journals, 2023)
In modern conditions, technologicalization of educational processes allows to achieve the expected result with less effort and time, improves the quality of teaching and increases its efficiency. Pedagogical innovation describes the consistent introduction of innovations into pedagogical activities. The educational system and process will develop according to the didactic possibilities of pedagogical innovations. This article describes the importance and importance of using innovative educational technologies in educational processes.
Keywords: Education, technology, innovation, experience, visibility, pedagogy.